2021
DOI: 10.1253/circj.cj-20-1096
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Characteristics of Coronary Artery Spasms Related to Atrial Fibrillation Ablation Procedures ― Large-Scale Multicenter Analysis ―

Abstract: A trial fibrillation (AF) ablation procedures are generally effective and safe; however, devastating complications occasionally occur. Coronary artery spasms (CASs) have recently been reported as a complication of AF ablation, and some patients develop serious Editorial p ????

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…However, in our study, 7 out of 9 patients had CAS directly after the transseptal puncture before the RFCA, suggesting no effect of the thermal energy. Nakamura et al reported the CAS related to the AF ablation procedure [16]. CAS associated with AF ablation occurred in 0.19% (42 of 22,232) and CAS occurred before the ablation in 21%.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, 7 out of 9 patients had CAS directly after the transseptal puncture before the RFCA, suggesting no effect of the thermal energy. Nakamura et al reported the CAS related to the AF ablation procedure [16]. CAS associated with AF ablation occurred in 0.19% (42 of 22,232) and CAS occurred before the ablation in 21%.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the Journal, based on their corresponding large-scale multicenter study, Nakamura et al 9 clearly demonstrate an incidence of CAS related to AF ablation of 0.19% (42/22,232), and CAS was the major cause of STE during PVI ablation. They performed emergency CAG in 88% (37/47) of the patients, and reversible spastic lesions occurred in all (29/29) patients who had continued STE during CAG.…”
Section: Ste During Catheter Ablationmentioning
confidence: 98%
“…9 Therefore, from the point of view of "STE" including air embolisms or thromboembolisms, the clinical manifestation of STE may be more frequently observed, as Tang et al described. 8 The Table shows a comparison of the results from Nakamura et al 9 and Tang et al 8 In the former study, an autonomic imbalance was highly suggested as the cause of the STE (CAS) because it particularly occurred during cryoablation of the left PVs. Cryoablation is thought to have a strong effect on the…”
Section: Ste During Catheter Ablationmentioning
confidence: 98%
See 2 more Smart Citations